Effects of different coating materials on three-dimensional optical scanning accuracy. (April 2019) - Pereira, João Rogério Machado; de Lima e Silva Penz, Ivan; da Silva, Fabio Pinto
The processes of three-dimensional optical scanning depend on the reflection of the surface to be digitized. To scan specular or translucent surfaces, it is necessary to apply a coating material which interferes with the accuracy of the three-dimensional measurements. This study proposes the use of gold, silver, platinum, and carbon by sputtering to coat the surfaces to be scanned. The effects of these materials on the accuracy of the three-dimensional scanning were evaluated and compared with those of two frequently used materials, namely, talc and non-aqueous wet developer for penetrant testing. To verify the resulting geometric variations, specimens were scanned before and after the application of each coating material. The results showed that the intrinsic errors of the three-dimensional scanning process, such as the registration of several point clouds, can have more significant effects than the coating material used. Measurements taken from a single point cloud showed dimensional tolerances of approximately 0.01 mm for gold, platinum, and carbon coating. These coatings offer significantly higher accuracy than the traditionally used developer and are suggested for accurate three-dimensional scanning of specular and translucent surfaces.